Effect of Strategic Planning of Human Resources in Management Performance - Ahmad Abujraiban; Gabriel J. Assaf (Civil Engineering Journal, 2022)
Strategic planning is an important stage in the administrative process, as it is considered a specific thinking process and style of work that enables the company to choose the best alternatives that correspond to the company's capabilities and the goals it seeks to achieve. This study aimed to find out the impact of strategic planning for human resources with its dimensions (environmental variables, needs assessment, dealing with results, human resources plan) on the performance of project management with its dimensions (time, cost, safety, quality), and to determine the strategic interaction between (HRP) on the performance of project management in infrastructure contracting companies and its role in facing external challenges. The study used the descriptive approach, through which the researcher developed a scale to answer the questions of the study. The study sample consisted of 120 employees in infrastructure contracting companies, they were divided into non-overlapping groups. The results showed the impact of strategic planning for human resources on the performance of construction project management and its contribution to raising the level of readiness of construction companies in facing external challenges and enabling them to compete with international companies, in addition to the contribution of strategic planning in facing the negative effects resulting from the Corona pandemic. The results are according to the company's age, capital, and the size of the company's project. The results of the study also showed that strategic human resource planning helps project management officials in the early detection of expected danger areas and attracts well-equipped workers with the appropriate skills to work efficiently. Doi: 10.28991/CEJ-2022-08-08-014 Full Text: PDF